Therapeutic potential of berries in age-related neurological disorders - Norouzkhani, Narges; Afshari, Shaghayegh; Sadatmadani, Sayedeh-Fatemeh; Mollaqasem, Mohammad Mahdi; Mosadeghi, Shakila; Ghadri, Hani; Fazlizade, Safa; Alizadeh, Keyvan; Akbari Javar, Pouyan; Amiri, Hamidreza; Foroughi, Elaheh; Ansari, Arina; et al. (Frontiers in Pharmacology, 2024)
Aging significantly impacts several age-related neurological problems, such as stroke, brain tumors, oxidative stress, neurodegenerative diseases (Alzheimer's, Parkinson's, and dementia), neuroinflammation, and neurotoxicity. Current treatments for these conditions often come with side effects like hallucinations, dyskinesia, nausea, diarrhea, and gastrointestinal distress. Given the widespread availability and cultural acceptance of natural remedies, research is exploring the potential effectiveness of plants in common medicines. The ancient medical system used many botanical drugs and medicinal plants to treat a wide range of diseases, including age-related neurological problems. According to current clinical investigations, berries improve motor and cognitive functions and protect against age-related neurodegenerative diseases. Additionally, berries may influence signaling pathways critical to neurotransmission, cell survival, inflammation regulation, and neuroplasticity. The abundance of phytochemicals in berries is believed to contribute to these potentially neuroprotective effects. This review aimed to explore the potential benefits of berries as a source of natural neuroprotective agents for age-related neurological disorders.